(untitled) (Baghdad Science Journal, 2022)
Nitrogen dioxide NO2 is one of the most dangerous contaminant in the air, its toxic gas that cause disturbing respiratory effects, most of it emitted from industrial sources especially from the stack of power plants and oil refineries. In this study Gaussian equations modelled by Matlab program to state the effect of pollutant NO2 gas on area around Durra refinery, this program also evaluate some elements such as wind and stability and its effect on stacks height. Data used in this study is the amount of fuel oil and fuel gas burn inside refinery at a year 2017. Hourly April month data chosen as a case study because it’s unsteady month. After evaluate emission rate of the all fuel and calculate exit velocity from stack (consider all refinery unit is a point), effective height resulted. Effective height is test with other atmospheric element and with stability, and there is direct relation with unstable turner classes. After Gaussian model implemented results show that most pollutant area from pollutant of NO2 is Al-Jadriyah and Al-Karada area, this area is about 3-5 kilometer from the refinery point. The wind direction domain is from the south to south-east, thus most flow is to north, north-west and the pollutant level of NO2 is over the national ambient air quality standard in this area.